Intrastriatal Memantine Infusion Dampens Levodopa-Induced Dyskinesia and Motor Deficits in a Mouse Model of Hemiparkinsonism - Ogawa, Masatoshi; Zhou, Yu; Tsuji, Ryosuke; Kasahara, Jiro; Goto, Satoshi (Frontiers in Neurology, 2019)
Although the administration of dopamine precursor levodopa remains as the mainstay for the treatment of Parkinson’s disease, long-term exposure to levodopa often causes a disabling complication, referred to as levodopa-induced dyskinesias. Therefore, the development of new therapeutic interventions to dampen levodopa-induced dyskinesias and parkinsonian motor deficits is needed in the treatment of Parkinson’s disease. Intracerebral brain infusion has the merit of being able to specifically deliver any drug into any brain part. By using an intracerebral infusion system equipped with implantable, programmable, and refillable pumps, we show herein that continuous intrastriatal administration of memantine, which is a non-competitive N-methyl-D-aspartate receptor antagonist, attenuates levodopa-induced dyskinesias and parkinsonian signs in 6-hydroxydopamine-lesioned hemiparkinsonian mice that received daily levodopa treatment. Corroborating the general thought that over-activation of the striatal N-methyl-D-aspartate receptor function might generate levodopa-induced dyskinesias and parkinsonism, our results suggest that a continuous intrastriatal memantine infusion can be beneficial for the management of Parkinson’s disease with levodopa-induced dyskinesias. Our study also provides indications for the prototypic use of pharmacological deep-brain modulation through intracerebral infusion systems for treating medically-intractable movement disorders.